The FXII c.-4T>C Polymorphism as a Disease Modifier in Patients With Hereditary Angioedema Due to the FXII p.Thr328Lys Variant - Corvillo, Fernando; Morena-Barrio, María Eugenia de la; Marcos-Bravo, Carmen; López-Trascasa, Margarita; Vicente, Vicente; Emsley, Jonas; Caballero, Teresa; Corral, Javier; López-Lera, Alberto (Frontiers in Genetics, 2020)
Background: Hereditary Angioedema due to the Thr328Lys variant in the coagulation Factor XII (HAE-FXII) affects mainly women in whom the symptomatology is dependant on high estrogen levels. Clinical variability and incomplete penetrance are challenging features that hinder the diagnosis and management of HAE-FXII. The c.-4T>C Kozak polymorphism is the only common variation accounting for FXII plasma levels and was previously shown to modify the course of HAE due to C1-Inhibitor deficiency. Objectives: To assess the influence of the c.-4T>C polymorphism on disease expression in 39 Spanish HAE-FXII index patients. Methods: The c.-4T>C polymorphism was sequenced by the standard Sanger method and HAE severity was calculated according to the score by Cummings et al. The activation of the contact system was quantified by the kallikrein-like activity of plasma in chromogenic assays upon activation with high-molecular-weight dextran sulphate. Results: The c.-4CC genotype was overrepresented in the studied cohort: 82% were CC-homozygous (expected frequency=59%) and 18% were CT-heterozygous (expected frequency=39%) (p=0.001). Patients with a c.-4CC genotype exhibited higher kallikrein-like activity (0.9659±0.1136) than those with a c.-4TC genotype (0.7645±0.1235) (p=0.024) or healthy donors. Moreover, the polymorphism influenced HAE-FXII severity score (c.-4CC=4.43±2.28 versus c.-4TC=2.0±1.15; p=0.006) but not the degree of estrogen dependence or time until remission. Conclusions: The c.-4T>C polymorphism is overrepresented in a Spanish HAE-FXII cohort and significantly influences the degree of contact system activation and the clinical severity of the disease. Clinical Implications: The c.-4T>C polymorphism is a genetic disease modifier that can help predict the penetrance of HAE-FXII symptoms.